2020
DOI: 10.2217/cer-2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

Golimumab improves patient-reported outcomes in daily practice of inflammatory rheumatic diseases in Germany

Abstract: Aim: To analyze the quality of life (QoL), work productivity and activity impairment (WPAI) and healthcare resource utilization (HCRU) in rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) patients receiving golimumab under routine clinical settings in Germany. Materials & methods: Prospective observational study, GO-ART, analyzed changes in WPAI, QoL and HCRU during 24 months of golimumab therapy. Results: Seven hundred and forty-eight patients (RA = 250, PsA = 249 and AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
2
2
1
Order By: Relevance
“…Compared with previous real-world evidence on golimumab from the non- interventional GO-ART study in Germany, the present study demonstrated more pronounced improvements in TWPI and activity impairment in RA, axSpA and PsA patients ( 19 ). Our study also demonstrated higher improvements in QoL at month 3 and 24 than the GO-ART study ( 19 ). These differences may be the result of a higher proportion of biologic naive patients in this study compared to the GO-ART study (77.3 vs. 67.5%).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Compared with previous real-world evidence on golimumab from the non- interventional GO-ART study in Germany, the present study demonstrated more pronounced improvements in TWPI and activity impairment in RA, axSpA and PsA patients ( 19 ). Our study also demonstrated higher improvements in QoL at month 3 and 24 than the GO-ART study ( 19 ). These differences may be the result of a higher proportion of biologic naive patients in this study compared to the GO-ART study (77.3 vs. 67.5%).…”
Section: Discussioncontrasting
confidence: 87%
“…Although these data are in line with other reports indicating that 33.3 to 54.0% of RA patients in Germany are unemployed for any reason ( 18 , 19 ), such a high proportion of unemployed patients could limit the power to detect the impact of golimumab on absenteeism in our study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…(35,36,30,41). Health-related QoL improvements were demonstrated in the RWE studies, GO-NICE and GO-ART, that were consistent with EQ-5D-3L data in the GO-BEYOND pooled analysis (42,43). These studies represent a large body of evidence that support the findings in the GO-BEYOND pooled analysis, which showed large proportions of patients achieving meaningful improvements in disease activity in populations of RA, PsA and axSpA patients who have experienced difficulties and setbacks with previous TNFαi treatments.…”
Section: Discussionsupporting
confidence: 79%
“…Current evidence also supports prescribing bDMARDs or tsDMARDs as first‐line agents in treatment‐naive patients due to similar or greater treatment efficacy as well as cost savings (37–40). Additionally, bDMARDs and tsDMARDs have been reported to help patients regain normal physical function and improve work productivity (41–45), which could generate additional active and productive hours, resulting in a positive impact on the German economy, as shown by Himmler et al (46). However, as existing health care systems do not provide adequate cover for advanced medications in every instance, rheumatologists may not yet prefer them as first‐line therapy.…”
Section: Discussionmentioning
confidence: 99%